PENGARUH SARANA PRASARANA TERHADAP MINAT BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SEKOLAH MENENGAH PERTAMA EL DZIKR BOARDING SCHOOL - Nurwahyudha, Ilham; Abbas, Ngatmin; Widoyo, Agus Fatuh (Jurnal Manajemen Pendidikan, 2025)
The quality of educational facilities and infrastructure plays a crucial role in creating an effective and conducive learning environment, especially in religious-based schools such as Islamic boarding schools. However, students’ learning interest is also influenced by various other factors. This study aims to determine the influence of the quality of facilities and infrastructure on students’ interest in learning Islamic Religious Education (PAI) at SMP El Dzikr Islamic Boarding School Kecamatan Bulu Kabupaten Sukoharjo in the 2024/2025 academic year. This research employs a quantitative approach with an associative type of study. The sample consisted of 30 eighth-grade students selected through total sampling. The main instrument used was a structured questionnaire, which had been tested for validity and reliability. Data were analyzed using descriptive statistics, Pearson Product Moment correlation, and simple linear regression. The results indicated that both the quality of facilities and students’ learning interest fell into the “moderate” category. However, statistical tests revealed no significant effect between the quality of facilities and learning interest (r = 0.336; sig = 0.070). This suggests that while there is a positive trend, the effect is not statistically significant.